PPARalpha regulates the production of serum Vanin‐1 by liver. Issue 22 (15th October 2013) - Rommelaere, Samuel; Millet, Virginie; Gensollen, Thomas; Bourges, Christophe; Eeckhoute, Jérôme; Hennuyer, Nathalie; Baugé, Eric; Chasson, Lionel; Cacciatore, Ivana; Staels, Bart; Pitari, Giuseppina; Galland, Franck; et al.
Abstract : The membrane‐bound Vanin‐1 pantetheinase regulates tissue adaptation to stress. We investigated Vnn1 expression and its regulation in liver. Vnn1 is expressed by centrolobular hepatocytes. Using novel tools, we identify a soluble form of Vnn1 in mouse and human serum and show the contribution of a cysteine to its catalytic activity. We show that liver contributes to Vanin‐1 secretion in serum and that PPARalpha is a limiting factor in serum Vnn1 production. Functional PPRE sites are identified in the Vnn1 promoter. These results indicate that serum Vnn1 might be a reliable reporter of PPARalpha activity in liver. Abstract : The Vnn1 pantetheinase is expressed in liver and secreted in serum. The vnn1 gene is a target of PPARα regulation. The level of serum Vnn1 production reflects PPARα activation in liver.